Characterization of Nanoparticles from Organic plant extracts using Multiple Drug Resistant Staphylococcus Aureus (MRSA) - SINAN MOHAMMED HASAN (International Journal of Pharma and Bio Sciences, 2018)
Nanotechnology is a sprouting interdisciplinary field of research interspersing material science, bionanoscience and technology. Moreover, functionalized, biocompatible and inert nanomaterial’s have potential applications in dealing Drug-resistant bacteria. Several studies have established the bactericidal effect of Nano silver in Gram negative and Gram positive bacteria, but the bactericidal mechanism of this compound has not been clearly elucidated. Silver nanoparticles have also been found to exert antibacterial activity against some drug-resistant bacteria. In the present study, we report the effect of three nanoparticle sizes (10, 30–40, and 100 nm) against MRSA. The nano materials measured in the SEM analysis shows that the size of the materials ranges from 80-120nm. The Kirby Buer test clearly indicates that the zone of inhibition to the MRSA was higher in the green AgNo3 nano particles at a particular concentration. These results indicate that the Green synthesized nano materials are effective in control disease causing microorganisms.